Implementation of Wadi'ah Academic In Sharia Banking - Choiriyah Choiriyah; Dwi Noviani; Richway Richway (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2023)
Public interest in muamalah according to shari'ah is a growing factor in the Indonesian economy. To develop society, the principle of Islamic Banking Institutions or Syari'ah Banking is to dismantle the interest system and replace it with a system for measuring the results of savings and loan operations. The most common form of fundraising contract in Islamic banks is the savings contract, which is also known as the wadi'ah contract. This study uses a constructive paradigm with a qualitative descriptive analysis for this type of research conducted on the literature. To process data, users use two types: secondary data and primary data. Data collection techniques are carried out using documentation studies. Data analysis uses content analysis with a more thorough process which includes categorization and selection in an in-depth format. In the process of collecting and analyzing data, researchers used two models of triangulation of sources. According to evidence, Wadi'ah helps those in need. Based on its application in Islamic banking, the term "wadi'ah contract" is divided into two categories, namely "Safe Keeping" and "Safe Deposit Box". "Safe Keeping" refers to the safekeeping of documents, contracts and other important documents, while "Safe Deposit Box" refers to the safekeeping of important papers, contracts and other documents. Every sharia banking organization must carry out its banking activities in accordance with Islamic sharia principles, especially those related to credit procedures. Islamic banking not only has a destination, but also has various problems. Including sharia products and tabling based on wadi'ah contracts.